Access to Information on Family Planning (FP) Methods Among Married Women of Reproductive Age in Ilala District, Dar es Salaam Tanzania - Ndumbaro, Faraja; Ochieng, Lucy M (University of Dar es Salaam Library Journal, 2021)
The paper reports the results of the study on access to information on family planning (FP) methods among urban married women of Ilala district, Dar es Salaam. In particular, the study assessed patterns to which married women access information on FP methods and challenges they face in the process. In total 119 married women attending maternal clinics at Buguruni, Amana, Mnazimmoja and Muhimbili hospitals were conveniently selected. Besides, 8 maternal health service providers were purposively selected from the four hospitals. Qualitative data were collected using key informant interviews while quantitative data were collected through face to face questionnaire. Notably, maternal health service providers, friends, neighbours and relatives were the main sources of contraceptive information among married women. Women ' s employment status, spouse ' s disapproval, formats and language of information contents are the main factors determining access to information on contraceptive methods. Results further show that women ' s levels of education correspond with their perceptions on challenges in accessing contraceptive information. It is concluded that maternal health clinics are not the only hubs for accessing information on contraception but also platforms in which knowledge is created and shared among women and between women and health service providers. The study recommends partners ' involvement in clinics and repackaging information as mechanisms to increase access to and eventually effective utilization of information on family planning among married women.